2012
DOI: 10.1007/s00540-012-1477-4
|View full text |Cite
|
Sign up to set email alerts
|

A randomized comparison of the i-gel and the ProSeal laryngeal mask airway in pediatric patients: performance and fiberoptic findings

Abstract: Both the pediatric i-gel and the PLMA were successfully inserted in children. The fiberoptic view was better with the i-gel than with the PLMA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 13 publications
3
41
1
1
Order By: Relevance
“…The mean oropharyngeal leak pressure with the i-gel was between 21 and 28 cmH 2 O. Gasteiger et al [12] and Fukuhara et al [13] found no significant differences between the devices. The largest trial in this group was by Tokgoz et al [14] and included i-gel sizes 1-2.5.…”
Section: Study Selection Bias Information Bias Measurement Errors Conmentioning
confidence: 91%
See 3 more Smart Citations
“…The mean oropharyngeal leak pressure with the i-gel was between 21 and 28 cmH 2 O. Gasteiger et al [12] and Fukuhara et al [13] found no significant differences between the devices. The largest trial in this group was by Tokgoz et al [14] and included i-gel sizes 1-2.5.…”
Section: Study Selection Bias Information Bias Measurement Errors Conmentioning
confidence: 91%
“…Lee et al [16] found a better fibreoptic view through the i-gel compared with the LMA Classic. The fibreoptic view seems to improve with increasing size of the patient [13] and probably reflects the change in laryngeal anatomy as a child grows.…”
Section: Fibreoptic View Of Larynx Through I-gelmentioning
confidence: 95%
See 2 more Smart Citations
“…또한 합병증 발생률(10% 이내)은 다른 SAD와 유사하거나 낮다고 평가되었다 [4]. 그러나 소아 환자에서 i-gel에 대한 기도 관리 연구는 제한적이다 [8][9][10]. Table 1에 표시하였다.…”
unclassified